Electric aircraft dynamics : a systems engineering approach - Vepa, Ranjan (Boca Raton, FL : CRC Press, 2020)
"Electric Aircraft Dynamics : A Systems Engineering Approach surveys engineering sciences that underpin the dynamics, control, monitoring, and design of electric propulsion systems for aircraft. It is structured to appeal to readers with a science and engineering background, and is modular in format. The closely linked chapters present descriptive material and relevant mathematical modeling techniques, followed by numerous design exercises that cover the assembly of systems that deliver, synergistically, the desired performance outcomes. Taken as a whole, this ground-breaking text equips professional and student readers with a solid foundation for advanced work in this emerging field"--
OCLC-licensed vendor bibliographic record.
Keywords: Electric airplanes -- Design and construction; Airplanes -- Motors; Airplanes -- Electric equipment; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Engineering / Mechanical